Guidelines for the Development of Learning Leadership of School Administrators under the Chaiyaphum Primary Educational Service Area Office 3 - Sanpanya, Supawit; Prasertphorn, Vanich (Journal for Developing the Social and Community, 2026)
Background and Aims: The 21st century is an era of transition for the global education system. Educational administrators today have shifted from their traditional management roles to roles of learning leadership. This research aimed to (1) examine the current conditions the desirable conditions and the priority needs of learning leadership of school administrators under the Chaiyaphum Primary Educational Service Area Office 3 and (2) propose guidelines for the development of learning leadership of school administrators under the Chaiyaphum Primary Educational Service Area Office 3 Methodology: A mixed methods research design integrating quantitative and qualitative approaches was employed. The sample consisted of 331 school administrators and teachers obtained through multistage random sampling. The research instruments included a five point Likert scale questionnaire with an overall reliability coefficient of 0.967 Descriptive statistics were analyzed and the modified Priority Needs Index (PNI_modified) was calculated. In addition semi structured interviews were conducted with three experts selected through purposive sampling to assess the appropriateness feasibility and usefulness of the proposed guidelines. Results: The findings revealed that the overall current condition of learning leadership of school administrators was at a high level whereas the desirable condition was at the highest level. The priority needs index of learning leadership was 0.29. The guidelines for developing learning leadership of school administrators consisted of six components namely (1) application of advanced technology in work practices with six guidelines (2) creativity with six guidelines (3) a learning supportive environment with four guidelines (4) team learning with four guidelines (5) the development of a learning culture with four guidelines and (6) self directed learning with four guidelines Conclusion: The Learning Leadership Development Guidelines aim to empower school administrators to become learning leaders through the following (1) application of advanced technology in work practices through clear and actionable policies, promoting IT skills, incorporating artificial intelligence, establishing mentoring systems, building networks, and measuring performance using technology. (2) creativity with Design Thinking, creating a space for flexible management, providing budgetary support, establishing management models, and conducting lessons learned for improvement. (3) a learning supportive environment through emphasizing the integration of a safe physical and mental space, building trust, employing positive psychology in management, and implementing supervision and monitoring. (4) team learning with building an atmosphere of trust, involving participation in decision-making, promoting lessons learned activities, and developing conflict management skills. (5) the development of a learning culture with defining shared values ​​and goals for the school, promoting unity, developing potential through challenging tasks, and reinforcing achievements through recognition and honor. and (6) Self-directed learning with driven by individual development plans aligned with the school’s vision, pursuing interests to maximize potential, implementing coaching systems to stimulate critical thinking and problem-solving, and creating platforms to celebrate achievements and inspire continuous improvement. These guidelines can be used to develop administrator development plans at the policy level to cultivate learning leadership and directly impacting teachers by increasing their chances of success in student achievement. Reduce administrative limitations and create excellence for educational institutions.